(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the measures implemented in Uzbekistan to improve the population’s housing conditions through financing from the state budget. Budget subsidies, support for mortgage lending, and the implementation of affordable housing programs play a critical role in ensuring access to housing. The study evaluates the effectiveness of government programs, financial mechanisms, and their impact on poverty levels using empirical methods. The paper concludes with recommendations for improving institutional frameworks and ensuring targeted and efficient allocation of budget funds in the housing sector.